Retrospective Study: Oral Therapy in Children with Atopic Dermatitis - Asmahani Thohiroh; Iskandar Zulkarnain (Faculty of Medicine, Universitas Airlangga, 2015)
Background: Atopic dermatitis (AD) is an inflammation skin characterized by itchy, chronic, residif; can occur in infant, child, and adult. The therapy for AD are divided into systemic and topical therapy. Systemic therapy includes antihistamine and corticosteroid. Purpose: To evaluate pattern of oral therapy in new child AD patient. Methods: Retrospective study methode was performed by evaluating medical records of new child AD patient who received oral therapy in Pediatric Division, Departement of Dermato-veneorology Dr. Soetomo General Hospital 2010 until 2012. The evaluated data include the patient's visitation, age, gender, time visit, patient's complain, periode of illness, history of atopy, physical examination, management, and follow up. Results: There were 558 patients (88.9%) of 628 new child AD patients who received oral therapy. Oral therapies were provided in form of antihistamine for 518 patients (92.8%), oral antibiotic for 129 patients (23.1%), and corticosteroid for 40 patients (7.2%). Patients who did not return to the hospital after first visitation were 461 patients (82.6%). Conclusions: Most of the child AD patient got an oral therapy. Most of the oral therapy was antihistamine.Key words: atopic dermatitis, child, oral therapy, retrospective.